Diagnostic accuracy of the diagnostic criteria for Temporomandibular Disorders for children aged 8-12 years - Katsikogianni, Eleni; Schweigert-Gabler, Susette; Krisam, Johannes; Orhan, Gül; Bissar, Abdul; Lux, Christopher J.; Schmitter, Marc; Giannakopoulos, Nikolaos Nikitas (Journal of oral rehabilitation, 2021)
Background and Objective Objective of this study was to determine whether the diagnostic accuracy of the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) is sufficient for use among schoolchildren aged 8-12 years. Methods This prospective cohort study on diagnostic accuracy with calibrated examiners was conducted among 533 children of both sexes aged 8-12 years, with and without TMD symptoms, selected randomly from the Rhein-Neckar district. Self-reporting of non-dental facial pain was used as the reference standard, against which we calculated the following for the pain-related items of the DC/TMD (index test): sensitivity, specificity, positive and negative likelihood ratios, diagnostic odds ratio, accuracy and 95% Wilson Score confidence intervals. We also calculated the area under the receiver-operating characteristic (AUROC) curve displaying sensitivity and specificity. Results Our final sample consisted of 282 children, half of whom reported having facial pain and 3.2% reported sounds from the temporomandibular joints (TMJs). Despite high specificity (90.78%; 95% confidence interval (CI): [84.86%; 94.53%]), sensitivity of the adapted DC/TMD for pain on maximum jaw opening was poor (37.59%; 95% CI: [30.02%; 45.81%]). For pain on palpation, more similar values were recorded for sensitivity (74.47%; 95% CI: [66.69%; 80.95%]) and specificity (70.21%; 95% CI: [62.21%; 77.14%]). The diagnostic odds ratio was >1 for both examinations. The AUROC for pain on opening was 68.39% (95% CI: [62.62%; 74.16%]), and for pain on palpation, it was 74.63% (95% CI: [69.45%; 79.81%]), whereas the combination of both resulted to an AUROC of 74.09% (95% CI: [68.96%; 79.21%]). It was not possible to measure the diagnostic accuracy of the DC/TMD regarding TMJ sounds or jaw-opening limitations, as they occurred too rarely in our sample. Conclusion In this study, the diagnostic accuracy of the DC/TMD for TMD-related pain in children was lower than that recorded for adults in previous studies.